Clinical Presentations of Patients with Hep B & C among Chronic Liver Disease at a Tertiary Care Hospital of Bahawalpur (Medical Forum Monthly, 2024)
Objective: The study was carried out to determine the different clinical presentations of patients with Hepatitis C and B related chronic liver disease.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Medical Unit III of Bahawal Victoria Hospital, Bahawalpur from January 2017 to December 2017.Materials and Methods: Only patients with chronic hepatitis C and B, leading to Chronic liver disease (CLD) were included in this study. Patients with CLD other than Hepatitis B and C viruses and pediatric age group (less than 13 years) were excluded from the study. The diagnosis was made with the help of clinical, biochemical and sonographic findings. Presenting complaints were recorded and detailed physical examination was done to look for different clinical presentations.Results: Total of 248 patients were studied. The most effected age group was between 50-59 years. Male gender was more commonly effected .The major presentations were of Upper Gastrointestinal bleeding (40.32%), abdominal distension (26.61%), and altered state of consciousness (11.29%), abdominal pain (10.48%), jaundice (7.25%), pedal edema (2.41%) and anorexia (1.61%). Chronic liver disease due to hepatitis C was greater than hepatitis B.Conclusion: Chronic liver disease due to Hep C was more common than Hep B. Upper GI bleed was the most common clinical presentation.